THE USE OF INTERNET AS A MEDIUM FOR LEARNING - Nyimas Yunierti Prihatin; Muhammad Abrar Parinduri; Siti Hawa Lubis; Halim Purnomo; Jesus Alberto Valero Mata (Tadrib: Jurnal Pendidikan Agama Islam, 2022)
This study aims to determine the use of the Internet as a learning medium for Islamic Religious Education at SMK Negeri 3 Palembang. The research is descriptive qualitative research using data collection instruments in the form of observation, interview, and documentation. The informants in this study were three Islamic Education teachers, the principal, vice principal, and students in grades X, XI, and XII. Data analysis is done by data reduction, then presenting and finally drawing conclusions from the data that has been obtained. The results showed that the utilization of the internet as a learning medium for Islamic religious education at SMK Negeri 3 Palembang has been going well, this is evidenced by: a). the internet helps facilitate access to Islamic Religious Education subjects, b). The availability of the Internet as a learning resource for Islamic religious education, c). The accuracy of the internet function as a learning resource, and d). The use of the internet can help learning achievement. The supporting factors for the use of the Internet as a learning medium for Islamic Religious Education at SMK Negeri 3 Palembang are: a). Teachers master information technology/computer science, b). Students master the operation of computers, schools provide computer facilities, and also subscribe to internet service providers at PT Telkom, and also provide internet hotspots that can be accessed in classrooms. While the inhibiting factors of using the internet as a learning media for Islamic Religious Education at SMK Negeri 3 Palembang are: a). Computer damage due to virus attacks, b). Internet network links and slow internet access because too many people use it simultaneously.